COMMD proteins function and their regulating roles in tumors - You, Guangqiang; Zhou, Chen; Wang, Lei; Liu, Zefeng; Fang, He; Yao, Xiaoxao; Zhang, Xuewen (Frontiers in Oncology, 2023)
The COMMD proteins are a highly conserved protein family with ten members that play a crucial role in a variety of biological activities, including copper metabolism, endosomal sorting, ion transport, and other processes. Recent research have demonstrated that the COMMD proteins are closely associated with a wide range of disorders, such as hepatitis, myocardial ischemia, cerebral ischemia, HIV infection, and cancer. Among these, the role of COMMD proteins in tumors has been thoroughly explored; they promote or inhibit cancers such as lung cancer, liver cancer, gastric cancer, and prostate cancer. COMMD proteins can influence tumor proliferation, invasion, metastasis, and tumor angiogenesis, which are strongly related to the prognosis of tumors and are possible therapeutic targets for treating tumors. In terms of molecular mechanism, COMMD proteins in tumor cells regulate the oncogenes of NF-κB, HIF, C-MYC, and others, and are related to signaling pathways including apoptosis, autophagy, and ferroptosis. For the clinical diagnosis and therapy of malignancies, additional research into the involvement of COMMD proteins in cancer is beneficial.